Pengaruh Work Life Balance, Decent Work, dan Job Satisfaction Terhadap Turnover Intention dengan Job Autonomy Sebagai Moderasi - Diana Dwi Tanti; Unik Dwi Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Decent work has become a career goal for every individual and a priority for many employers and policy makers who want to promote social justice. This study aims to explore the relationship between decent work, work-life balance, job satisfaction, job autonomy and turnover intention specifically among employees in manufacturing companies who are married and have children. Furthermore, this study used purposive sampling method to determine respondents. This research was conducted on 200 manufacturing employees of the home appliance industry in Jabodetabek. The data obtained were analyzed using the structural equation model (SEM) method. The results of this study indicate a negative effect of decent work on turnover intention, job satisfaction on turnover intention, and decent work on work life balance has a positive effect, decent work on job satisfaction has a positive but insignificant effect, work life balance on job satisfaction has a positive but insignificant effect. While the moderating effect of job autonomy has no significant effect on decent work on job satisfaction and also decent work on turnover intention. The managerial implications of this research are to provide input to company management in the manufacturing industry in Jabodetabek in overcoming employee turnover rates, especially for employees who are married and have children by increasing employee turnover.